Efficacy and safety of cisplatin + docetaxel + 5-FU + leucovorin + methotrexate and epirubicin combination chemotherapy for advanced esophageal cancer - Sung-Chi Yu; Shao-Syuan Tong; Yi-Ling Chen; Ya-Fu Cheng; Jin-Ching Lin; Ching-Yuan Cheng; Chang-Lun Huang; Wei-Heng Hu; Bing-Yen Wang (PLoS ONE, 2025)
Abstraction Esophageal cancer is a devastating disease. The cisplatin and 5-FU regimen is the most widely used concurrent chemoradiotherapy protocol for metastatic, unresectable advanced esophageal cancer in Asia. However, its effectiveness remains limited due to unsatisfactory outcomes. Therefore, we conducted a retrospective study to evaluate the efficacy and toxicity of Cisplatin + 5-FU combined with docetaxel, leucovorin, methotrexate, and epirubicin (CDFLME), a first-line multi-agent chemotherapy regimen used for the treatment of advanced esophageal cancer in Taiwan. We enrolled 94 patients in our study from January 2018 to June 2022. All patients were diagnosed with metastatic or unresectable advanced esophageal cancer. Among them, 81 patients received fluorouracil + cisplatin regimen serving as the control group, while 13 patients received the CDFLME combination regimen. Significant improvements were observed in the CDFLME group compared to the fluorouracil + cisplatin group in overall survival time, complete response rate, and disease control rate. No significant differences were noted in treatment-related deaths or grade 3–4 adverse events, except for grade 1–2 mucositis. Based on these findings, we conclude that the CDFLME regimen is a promising alternative treatment with relatively minor adverse events and is an effective protocol for patients with advanced esophageal cancer.